Clinicodemographic Profile and Outcome of Maintenance Hemodialysis Patients in a Tertiary Hospital of Central Nepal, Chitwan - Ghimire, M.; Vaidya, S.; Upadhyay, H.P. (Kathmandu University Medical Journal, 2020)
Background Maintenance hemodialysis is a popular treatment modality of renal replacement therapy for end stage renal disease patients; however their mortality seemed to be rising in our centre. There were no previous studies regarding the clinicodemographic profile and outcome of maintenance hemodialysis patients from this region. Objective This study was carried out with an objective to know the clinicodemographic profile and outcome of maintenance hemodialysis patients in our centre. Method This study was a hospital based prospective observational study carried out over a period of three year, from May 2016 to April 2019, in the hemodialysis unit of the department of nephrology. All the consecutive end stage renal disease patients on maintenance hemodialysis were included in the study. The patient’s demographic profile and outcome were studied and analysed using appropriate statistical tools. Result A total of 156 patients were enrolled in the study. Males were 96(61.5%) and females were 60(38.5%). The mean age of the patient was 52.2±15.6 years. The commonest causes of end stage renal disease and reasons for admission were Type 2 diabetes mellitus 68(43.6%) and volume overload with heart failure 101(64.7%) respectively. At the end of three years, 39(25%) were expired, 14(8.9%) were transferred to other centre and four (2.6%) underwent kidney transplantation. The average duration of hemodialysis was 20.3± 17.5 months. Majority of the patients 154(98.7%) had repeat admission ranging from 1 time 21(13.5%) to 10 times two (1.3%). There was a significant association between age ≥ 40 years and diabetes with mortality (p value < 0.003 and < 0.028 respectively). Conclusion The commonest cause of end stage renal disease and the reason of admission were Type 2 diabetes mellitus 68 (43.6%) and volume overload with heart failure 101 (64.7%) respectively. The overall mortality was 39 (25%) and the commonest cause of mortality was sepsis/health care associated pneumonia 30 (76.9%). There was significant association between age ≥ 40 years and diabetes with mortality (p value < 0.003 and < 0.028 respectively).